Digital poison? Three studies examining the influence of violent video games on youth. (September 2015) - Ferguson, Christopher J.; Barr, Hayley; Figueroa, Grace; Foley, Kimberly; Gallimore, Alexander; LaQuea, Rachel; Merritt, Alexandra; Miller, Stephanie; Nguyen-Pham, Hien; Spanogle, Cameron; Stevens, Julie; Trigani, Benjamin; et al.
Highlights: In two experimental studies, playing violent games did not increase youth aggression. Youth who played violent games were also no less empathic toward others. Youth with prior mental health symptoms were no more influenced by violent games. Correlationally, violent games and books did not predict aggression or civic behavior. Parental restrictions on gaming were not associated with positive outcomes. Abstract: The role of violent video games in the development of aggression and mental health issues in youth continues to be controversial in the scholarly community and general public. Compared to college students, few studies have directly examined the potential impact of violent video games on youth and current evidence is mixed. The current article attempts to address this with three studies examining violent game play in youth aged 12–18. In Study 1, youth were randomized to play closely matched action games with either violent or non-violent content. Youth were given the opportunity to act aggressively using an ice water task. Study 2 was a conceptual replication of Study 1, with slower narrative games rather than action games. Study 3 examined the issue in a correlational study of youth, contrasting exposure to violent video games in youth's personal lives to their exposure to violence in controversial books while controlling for other variables including family, peer and personality variables. None of the studies provided evidence for concerns linking video game violence to aggressive behaviors or reduced empathy in youth.